Intervenções sobre a tomada de decisão e a desvalorização pelo atraso em fumantes de tabaco - Barbosa, Arianne de Sá (2016)
Five articles derived from the Doctoral Degree: three theoretical and two empirical. The first one, "Multiple definitions of smokers and diagnosis of smoking: a systematic review", reviewed the scientific production that deals with definitions of smokers and other related dimensions. The second article, "Crossing the cloud of smoke: is smoking a decision?" is a narrative review of the literature that concluded smoking is a decision. "Sparks of a diagnosis: being a smoker is not synonymous with being a tobacco addict" is a thematic essay that defends the thesis that smoker is not synonymous with being chemically dependent of tobacco. The first empirical study, "Delay Discounting, executive functions and social-demographic profile of tobacco smokers," investigated the DD executive functions and social-demographic profile of two groups of smokers: 35 Smoking Cessation Group Waiting List Smokers (FLE) and 35 Smokers Not Seeking Treatment to Stop Smoking (FNBT). The DD was larger in the FLE group. Finally, the second empirical article was the study “Therapeutic Effects of Interventions about the Delay Discounting of Tobacco Smokers,” which investigated the evidences of therapeutic effect in interventions about the Attention, Memory and Executive Functions in two groups of smokers (35 FLE and 35 FNBT) as a main action to change the manner that these individuals make decisions.). The DD, the frequency of smoking behavior and the level of nicotinic dependency were reduced and executive functions of smokers of 20 smokers who adopted the Cognitive Training were improved (05 FLE and 15 FNBT).